Evaluasi Kualitas Pengalaman Pengguna pada Platform e-Learning Universitas Jenderal Achmad Yani - Tsaniabbad, Athaya; Mutaalim, Fadli; Pudjiantoro, Tacbir Hendro; Destiani, Dea (Jurnal Sains dan Teknologi (JSIT), 2025)
The utilization of e-learning platforms in higher education has become a fundamental necessity to support effective and efficient online learning processes. User experience (UX) quality plays a crucial role in determining the success of such platforms, both from technical and pedagogical perspectives. Universitas Jender al Achmad Yani (UNJANI), as a higher education institution, has developed its own e-learning system to facilitate technology-based instruction. This study aims to evaluate the UX quality of UNJANI’s e-learning platform. A mixed methods approach was employed, combining quantitative and qualitative methodologies. Quantitative data were collected through the distribution of the User Experience Questionnaire (UEQ) to 354 student respondents from four faculties. Meanwhile, qualitative data were gathered through in-depth interviews with 26 respondents to gain a more comprehensive understanding of user perceptions and experiences. The quantitative analysis revealed that the platform scored highest in the attractiveness and novelty dimensions (1.55), followed by clarity and efficiency (1.50). However, the accuracy (0.78) and stimulation (0.85) dimensions indicated areas for improvement. The qualitative findings supported these results and further uncovered technical issues and a demand for more innovative and interactive features. The study concludes that UNJANI’s e-learning platform provides a relatively positive user experience, yet further development is required to enhance system stability and the effectiveness of features supporting online learning.